Pain assessment and clinical profile of burn patients - Banotra, Ankush; Kumari, Monika; Wani, Mumtaz Din; Banotra, Pankaj (International Journal of Advances in Medicine, 2022)
Background: Burn injuries are a major global public health concern with up to 52% of burn patients suffering from chronic pain. The aim of the study was to asses clinical profile and management of pain in burn patients. Methods: The study was a prospective hospital-based study on a total of 300 patients admitted in burn unit of the department of surgery over a period of two years. BSA burns was determined by Wallace’s rule of nine in adults and in children by Lund and Browder chart. Pain was assessed using Wong-Baker FACES pain rating scale. Statistical analysis was done using SPSS program. Results: In the present study, most of the burns i.e., 46.7% were seen in <20 years age group, and more in male (58.7%) subjects. Accidental burns and superficial burns were the most common. There were 113 (53.3%) patients with pain score of 2 followed by 160 (53.3%) with pain score 3, 22 (7.3%) pain score 4 and 5 (1.7%) with pain score of 1. For pain management, 171 (57%) patients were given NSAIDS, 78 (26%) needed opioid and NSAIDs and 51 (17%) needed opioid only. Complications in our studied patients on follow up revealed 29 (9.7%) had PTSD, 22 (7.3%) had post burn contracture, 16 (5.3%) had post burn pain, 15 (5.0%) were having anxiety. Conclusions: Pain in burn victims is present throughout the rehabilitation and so should be dealt with multimodal specialties.